2017
DOI: 10.1002/ejoc.201701241
|View full text |Cite
|
Sign up to set email alerts
|

A Zwitterionic Palladium(II) Complex as a Precatalyst for Neat‐Water‐Mediated Cross‐Coupling Reactions of Heteroaryl, Benzyl, and Aryl Acid Chlorides with Organoboron Reagents

Abstract: The Suzuki–Miyaura cross‐coupling (SMC) reactions of several heteroaryl chlorides, benzyl chlorides, and aryl acid chlorides with (hetero)arylboron reagents have been investigated in the presence of [Pd(HL1)(PPh3)Cl2] (I) [HL1 = 3‐[(2,6‐diisopropylphenyl)‐1‐imidazolio]‐2‐quinoxalinide] as catalyst and K2CO3 as base in neat water. The synthesis of the heterocycle‐containing biaryls required the addition of 2 mol‐% of a phosphine ligand (PPh3 or X‐Phos). A combination of more than 115 substrates were screened an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 166 publications
1
3
0
Order By: Relevance
“…17, 153.37, 149.65, 148.82, 135.98, 132.26, 127.54, 126.52, 125.19, 123.98, 123.51, 123.43, 123.03, 122.36, 120.81, 120.62, 111.89. The spectral data matched those reported in the literature (Ramakrishna et al, 2017). 138.13, 137.10, 130.10, 129.67, 128.60, 127.12, 126.81, 52.11, 21.18.…”
Section: Nicotinic Acid and 3-methoxyphenylboronic Acid (3as Figure 4 Entry 45)supporting
confidence: 85%
“…17, 153.37, 149.65, 148.82, 135.98, 132.26, 127.54, 126.52, 125.19, 123.98, 123.51, 123.43, 123.03, 122.36, 120.81, 120.62, 111.89. The spectral data matched those reported in the literature (Ramakrishna et al, 2017). 138.13, 137.10, 130.10, 129.67, 128.60, 127.12, 126.81, 52.11, 21.18.…”
Section: Nicotinic Acid and 3-methoxyphenylboronic Acid (3as Figure 4 Entry 45)supporting
confidence: 85%
“…We have recently reported the synthesis of zwitterionic palladium complexes and their catalytic efficiency in Suzuki–Miyaura cross coupling (SMC) reactions. 11 In order to explore the mechanistic details of those reactions two quinoxaline based NHC-palladacycles were synthesized. It was found that these palladacycles were less efficient than the precursor imidazolium zwitterionic complexes in catalyzing the SMC reactions.…”
Section: Resultsmentioning
confidence: 99%
“…13 This reaction was applied to electron-deficient aryl chlorides only, while the products were obtained in up to 98% yield. Reddy et al developed a zwitterionic Pd(II) complex C4 (0.5 mol%) and utilized it for SM couplings of aryl or heteroaryl chlorides, 14 where triphenylphosphine (PPh 3 ) (2 mol%) was used as an additional ligand. The reactions of multiple heterocyclic aryl chlorides, including pyridine, pyrazine, quinoline, isoquinoline, and thiophene, afforded cross-coupling products 17-24 in yields of 80-95% (Scheme 6).…”
Section: Short Review Synthesismentioning
confidence: 99%